2018
DOI: 10.1038/s41467-018-03712-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin bismuth nanosheets from in situ topotactic transformation for selective electrocatalytic CO2 reduction to formate

Abstract: Electrocatalytic carbon dioxide reduction to formate is desirable but challenging. Current attention is mostly focused on tin-based materials, which, unfortunately, often suffer from limited Faradaic efficiency. The potential of bismuth in carbon dioxide reduction has been suggested but remained understudied. Here, we report that ultrathin bismuth nanosheets are prepared from the in situ topotactic transformation of bismuth oxyiodide nanosheets. They process single crystallinity and enlarged surface areas. Suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
482
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 774 publications
(500 citation statements)
references
References 44 publications
14
482
3
1
Order By: Relevance
“…The onset potentials for CO 2 RR and OER are approximately À 1.8 V and 1.0 V vs. Fc/Fc + , respectively. This value is considerably lower than the value of~6 mA cm À 2 reported by Han et al [20] in an aqueous bicarbonate medium with Bi nanosheet modified carbon paper as the cathode and Ir/C modified carbon paper as the anode. A two-compartment electrochemical cell was employed to conduct the artificial photosynthesis experiment (Figure 6b) with CoNC-400 modified carbon cloth (1 cm × 3 cm) as the cathode and anode.…”
Section: Concs With Size Controllable Co Nps Derived From Co-tcnq Andcontrasting
confidence: 64%
“…The onset potentials for CO 2 RR and OER are approximately À 1.8 V and 1.0 V vs. Fc/Fc + , respectively. This value is considerably lower than the value of~6 mA cm À 2 reported by Han et al [20] in an aqueous bicarbonate medium with Bi nanosheet modified carbon paper as the cathode and Ir/C modified carbon paper as the anode. A two-compartment electrochemical cell was employed to conduct the artificial photosynthesis experiment (Figure 6b) with CoNC-400 modified carbon cloth (1 cm × 3 cm) as the cathode and anode.…”
Section: Concs With Size Controllable Co Nps Derived From Co-tcnq Andcontrasting
confidence: 64%
“…Due to difficulties associated with the direct synthesis and engineering of metallic Bi nanostructures, it is more viable to start with precatalysts composed of oxides, oxyhalides, carbonates, or sulfides, and then cathodically convert them to metallic Bi for CO 2 RR. Following this guiding principle, our group reported the preparation of ultrathin Bi nanosheets from the in situ topotactic transformation of BiOI nanosheets ( Figure 8 a–c) . Interestingly, we found that the 2D geometry and single crystallinity were well‐preserved after the cathodic conversion due to the intrinsic structural correlation between BiOI and metallic Bi.…”
Section: Main Group Metal–based Electrocatalysts For Selective Co2rr mentioning
confidence: 91%
“…Liquid products (such as formate, methanol, ethanol, acetate, and so on) accumulated in the catholyte at the end of tests can be measured using proton nuclear magnetic resonance ( 1 H NMR). Alternatively, we find that ion chromatography is an effective tool for quantifying the amount of formate in the catholyte . It has a lower detention limit (≈100 ppb) than NMR (1–10 ppm), and is easier to operate.…”
Section: Fundamentals Of Electrochemical Co2 Reductionmentioning
confidence: 92%
See 1 more Smart Citation
“…For instance, Bi nanosheets catalyst that are generated from atomic‐thick Bi oxycarbonate nanosheets display a FE HCOO − of ≈100% at −0.9 V and this activity is partly attributed to the presence of Bi(101) and Bi(111) facets, which are demonstrated to lower free energy barrier for formation of *OCHO radical, facilitating CO 2 RR . Similar facet dependent DFT results with Sn, In and Bi catalysts were used as theoretical evidence to justify the catalytic activity of these catalysts for CO 2 RR . In addition, SnO 2 (110) is reported to play a positive role in dictating formate generation during CO 2 RR with a number of literatures with SnO 2 nanoparticle catalysts ascribing the importance of this facet …”
Section: Active Sites In Metal‐based Catalystsmentioning
confidence: 86%